Electrical Energy Monitoring System and Automatic Transfer Switch (ATS) Controller with the Internet of Things for Solar Power Plants - Novi Kurniawan (SHM Publisher, 2020)
Internet of Things is a technology that connects communication devices with electronic devices that are used everyday using the internet as a medium to communicate between devices and users. The use of IoT technology can be implemented in solar power generation systems. The IoT technology implemented in this study is to monitor and control the use of batteries in solar power plants. Current technology, battery usage can only be monitored closely to get information about battery capacity and battery usage. When the battery is empty or cannot be used to meet electricity needs, it is not equipped with a diversion of existing electricity sources such as PLN electricity. So, we need a renewable technology to get information about batteries and transfer of electricity sources that can be accessed remotely and can be accessed via the internet. The design of this smart monitoring system has stages, namely planning,design , coding , and test . The results of this study are able to see data in the form of battery capacity, electric current and electric power used in Android applications. The data is obtained from sensors that are on smart monitoring connected to the internet network and stored on a database server. Then the data residing on the database server will be retrieved by the application to be displayed to users in the form of graphics and usage lists. Furthermore, the Automatic Transfer Switch system works if the battery capacity sensor has read less than 11.4V then the relay will automatically transfer electricity to PLN. The Android smartphone application is used as a monitoring tool to view data in realtime.